1975
DOI: 10.1111/j.1476-5381.1975.tb07389.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Propranolol on Vascular Responses to Sympathetic Nerve Stimulation

Abstract: In an attempt to clarify the rǒle of the sympathetic neurone in the antihypertensive action of propranolol, the effect of this drug on responses to lumbar sympathetic nerve stimulation has been studied in the perfused hind‐limb of the dog. No consistent reduction of maximal or submaximal responses to nerve stimulation was produced by propranolol (10 to 100 μg/kg). In contrast, potentiation of nerve‐evoked responses, as well as those to injected noradrenaline, usually occurred. Dexpropranolol (50 μg/kg) had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1976
1976
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
4
1
Order By: Relevance
“…Despite the clear-cut b-dilatation in the small vessels, a reinforcement of the sympathetically evoked net increase of total vascular resistance was, however, not revealed when the dilator response was blocked by propranolol. This is in contrast t o the findings of Viveros, Garlick and Renkin (1968) and of Dawes and Faulkner (1975), who reported that @-blockade potentiated sympathetic vasoconstriction. This conclusion, however, was reached using constant flow perfusion.…”
Section: Discussioncontrasting
confidence: 90%
“…Despite the clear-cut b-dilatation in the small vessels, a reinforcement of the sympathetically evoked net increase of total vascular resistance was, however, not revealed when the dilator response was blocked by propranolol. This is in contrast t o the findings of Viveros, Garlick and Renkin (1968) and of Dawes and Faulkner (1975), who reported that @-blockade potentiated sympathetic vasoconstriction. This conclusion, however, was reached using constant flow perfusion.…”
Section: Discussioncontrasting
confidence: 90%
“…Several investigators have reported dilator responses to sympathetic nerve stimulation Jarhult, 1974, 1976;Tuttle and Moe, 1973;Viveros et al, 1968), whereas others have found none in animals that had received both an a-adrenoceptor antagonist and atropine (Belfrage and Rosell, 1976;Dawes and Faulkner, 1975;Glick et al, 1967;Folkow and Uvnas, 1950;Rosell and Belfrage, 1975;Youmans et al, 1955;Vatner and McRitchie, 1976). Viveros et al, (1968) observed vasodilation in the perfused gracilis muscle of the dog in response to sympathetic nerve stimulation after administration of dibozane and atropine, vasodilation that was then blocked by propranolol.…”
Section: Discussionmentioning
confidence: 99%
“…One of the more widely quoted papers is that of Viveros et al (1968) in which sympathetic nerve stimulation or norepinephrine given ia causes vasodilation in the perfused gracilis muscle in dogs treated with dibozane and atropine. However, other investigators have failed to identify such responses (Youmans et al, 1955;Glick et al, 1967;Rosell and Belfrage, 1975;Belfrage and Rosell, 1976;Folkow and Uvnas, 1950;Dawes and Faulkner, 1975;Vatner and McRitchie, 1976). Youmans et al (1955) suggested that the adrenoceptors that subserve vasodilation in dog skeletal muscle (/S-2 by modern terminology) are under only hormonal (epinephrine) control and do not respond to sympathetic nerve stimulation.…”
Section: Evidence For Lack Of Innervation Of /?-2 Adrenoceptors In Thmentioning
confidence: 99%
“…7 This action has also been suggested as contributing to the hypotensive effect of propranolol, although Dawes and Faulkner could not find evidence of such effect in the circulatory response to lumbar sympathetic nerve stimulation in the hind limb of the dog. 5 The likelihood of testing these possibilities in man is limited. One might examine the effect of stimuli capable of eliciting a neurally mediated cardiovascular reaction, and evaluate in qualitative and quantitative terms the variations in response induced by long-term beta adrenergic…”
mentioning
confidence: 99%